2013
DOI: 10.21829/azm.2013.291399
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad de murciélagos (Mammalia, Chiroptera) en la ciudad de Lules, Tucumán

Abstract: ABSTRACT. We identified the species of bats and their roosts in the urban area of Lules, Tucuman. This is the first systematic study in Argentina in an urban area. Seven species were collected mainly housed in roofs, outstanding the collection of Eumops glaucinus, representing the second record of this species for the province.En Argentina, el conocimiento sobre los murciélagos urbanos y sus refugios es escaso (Romano et al. 1999;Vaccaro & Varela 2001;Varela et al. 2004), y no se han realizado estudios sistemá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
5
0
5
Order By: Relevance
“…Although the capture of large numbers of individuals of this species is unusual, the recorded abundance is likely because the mist nets were placed at strategic points, after we discovered a small colony sheltered within an abandoned house. In other studies in Argentina, this species was also found roosting inside buildings (López Berrizbeitia & Díaz 2013;Lutz 2013). The high abundance of Sturnira lilium is also coincident with other several studies made in tropical (Kalko & Handley 2001) and subtropical environments (Moya et al 2008;Gamboa Alurralde et al 2016), where bat assemblages are dominated by frugivorous species.…”
Section: Discussionmentioning
confidence: 57%
“…Although the capture of large numbers of individuals of this species is unusual, the recorded abundance is likely because the mist nets were placed at strategic points, after we discovered a small colony sheltered within an abandoned house. In other studies in Argentina, this species was also found roosting inside buildings (López Berrizbeitia & Díaz 2013;Lutz 2013). The high abundance of Sturnira lilium is also coincident with other several studies made in tropical (Kalko & Handley 2001) and subtropical environments (Moya et al 2008;Gamboa Alurralde et al 2016), where bat assemblages are dominated by frugivorous species.…”
Section: Discussionmentioning
confidence: 57%
“…In South America, Eumops glaucinus is known to occur in the north of Argentina, Bolivia, Brazil, Colombia, Ecuador, Guyana, Paraguay, Peru, and Venezuela (Gardner 2008. In Argentina, it can be found in Chaco, Jujuy, La Rioja, Misiones, Salta, and Tucuman (Vaccaro 1992, Barquez et al 1999, López Berrizbeitia and Díaz 2013, Gamboa Alurralde et al 2016). This species was recently reported by Pavé et al (2017) from Santa Fe province, based on a specimen collected in the city of Santa Fe (La Capital department).…”
Section: Discussionmentioning
confidence: 99%
“…Bats have been intensively studied in Argentina in recent decades, but the majority of these studies were conducted in the northwest region of the country, mainly in the provinces of Jujuy, Salta, Tucumán, Catamarca, and La Rioja (Mares et al 1989, 1995, 1996, Barquez and Ojeda 1992, Barquez et al 1993, Barquez and Díaz 2001, Barquez 2006, López Berrizbeitia 2013, Gamboa Alurralde et al 2016, Urquizo et al 2017. Knowledge on the diversity and distribution of the Santa Fe bat fauna has increased along the last century, but only due to reports based on occasional collections.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that E. glaucinus also has been found in urban environments along Gamboa Alurralde et al | New records of bats from Argentina its distribution in America (Best et al 1997). In the northwestern Argentina, this species has been collected in the cities of San Miguel de Tucumán and San Isidro de Lules, in Tucuman Province (López Berrizbeitia and Díaz 2013).…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%